A method of formation of a lead-acid battery
Patent Information
- Application Number
- CN202511506621.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-10-21
AI Technical Summary
[0005]但上述两个公开的专利文献,使用真空化成后电池的化成周期的缩短幅度仅为15%-30%,远远无法满足电池行业对快速化成提升生产效率的要求
[0006]本发明的目的在于解决上述现有技术的不足,从而提供一种铅酸蓄电池高效化成方法。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of lead-acid battery technology, specifically to a method for forming a lead-acid battery. Background Technology
[0002] Currently, most lead-acid battery formation processes employ internal formation (acid density 1.20±0.05g / ml). In order to shorten the formation cycle, vacuum formation technology has become a key means to improve the formation efficiency of lead-acid batteries.
[0003] For example, CN 115020837 B discloses a full negative pressure vacuum charging process and equipment for lead-acid batteries. The negative pressure plate is connected to the acid pot on the battery's acid filling port. The charging process maintains a negative pressure of 0.03~0.1 MPa. It adopts a five-charge-discharge process with a total of 17 steps and takes about 36 hours, which shortens the formation time by 15%~25% compared to the ordinary formation method.
[0004] CN 120149580 A discloses a vacuum formation process and apparatus for lead-acid batteries. The assembled battery is placed in a vacuum formation apparatus for pretreatment (vacuum degree -0.06MPa to -0.08MPa, pretreatment time 15-20 minutes). Then, electrolyte at a pre-set temperature is injected into the battery under vacuum conditions. Finally, while maintaining the vacuum state, the battery is subjected to segmented constant current charging. The formation time for 12V energy storage lead-acid batteries and 12V power lead-acid batteries is shortened by approximately 30% compared to traditional formation processes (from 96-97 hours to 67-72 hours).
[0005] However, the two publicly available patent documents mentioned above show that the reduction in the battery formation cycle after using vacuum formation is only 15%-30%, which is far from meeting the battery industry's requirements for rapid formation to improve production efficiency. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high-efficiency formation method for lead-acid batteries.
[0007] A method for forming a lead-acid battery includes the following steps:
[0008] ① Add acid to lead-acid batteries using a sulfuric acid solution with a density of 1.02 g / ml to 1.06 g / ml and containing 0.5 wt% to 1 wt% metal sulfates;
[0009] ② Place the acid-added battery in a vacuum chamber, connect the charging circuit and begin the formation process. The formation process includes two stages: a small-current charging stage to activate the electrode, and a vacuum formation and rapid electrolyte evaporation stage. During the small-current charging stage to activate the electrode, the absolute pressure inside the vacuum chamber is controlled at 40~60 kPa. During the vacuum formation and rapid electrolyte evaporation stage, the absolute pressure inside the vacuum chamber is controlled at 15~60 kPa.
[0010] ③ After the formation process is complete, add a compound electrolyte to the battery;
[0011] ④ Add a small amount of hexadecyl alcohol to the battery.
[0012] Step ②, the small-current charging and electrode activation stage, specifically includes the following steps:
[0013] Charge at a current of 0.02C20±0.5A for 0.2~0.3h, then charge at a current of 0.15C20±3A for 0.2~0.5h. The electrolyte temperature during the formation process is controlled at 45℃~60℃ by setting the absolute pressure inside the vacuum chamber.
[0014] Step ②, the vacuum formation and rapid electrolyte evaporation stage, specifically includes the following steps:
[0015] Charge at a current of 0.45C20±5A for 2~2.5h, then charge at a current of 0.35C20±5A for 2~2.5h. During the formation process, the temperature of the electrolyte is controlled at 50℃~65℃.
[0016] The electrolyte density after formation was in the range of 1.28 g / ml to 1.30 g / ml.
[0017] During the vacuum formation and rapid evaporation of the electrolyte stage, the absolute pressure inside the vacuum chamber is controlled at 15~30 kPa.
[0018] The metal sulfate in step ① is at least one of potassium sulfate and sodium sulfate.
[0019] The metal sulfates in step ① are potassium sulfate and sodium sulfate, with the mass ratio of sodium sulfate to potassium sulfate being 1:1 to 1:2.
[0020] After adding the compound electrolyte in step ③, the electrolyte level inside the battery must submerge the battery busbar and the butt welds connected to the busbar.
[0021] The weight of the compound electrolyte in step ③ is 5wt%~10wt% of the weight of the acid added in step ①;
[0022] The density of the compound electrolyte is 1.28 g / ml to 1.30 g / ml;
[0023] The compound electrolyte is prepared by adding propylene glycol to a 1.30 g / ml sulfuric acid solution and stirring to mix it. The mass fraction of propylene glycol in the compound electrolyte is 2 wt% to 15 wt% of the sulfuric acid solution.
[0024] In the compound electrolyte, propylene glycol accounts for 3wt% to 8wt% of the sulfuric acid solution.
[0025] Step ③ specifically involves heating hexadecanoic acid to 60℃~70℃ and adding 1ml~5ml to each cell of the battery.
[0026] This invention utilizes a low-density sulfuric acid solution for acidification (1.02 g / ml~1.06 g / ml), and employs vacuum extraction during the formation process to control the electrolyte temperature and the evaporation rate of water in the electrolyte, thereby achieving highly efficient formation. Specifically, the low-density sulfuric acid solution for acidification helps control the electrolyte temperature in the initial stages of formation, reduces electrode polarization during the formation process, improves formation efficiency, and saves formation energy. Furthermore, the positive electrode active material obtained under low acid density conditions has a higher α-PbO2 content, which is beneficial for extending battery life. The vacuum process during formation promotes the desorption of hydrogen and oxygen generated on the electrode surface, increasing the effective reaction area and significantly improving formation efficiency. Furthermore, the vacuum level determines the boiling point of the electrolyte. By appropriately setting the vacuum level, the electrolyte temperature is prevented from becoming too high, thus ensuring battery performance, while also allowing for rapid evaporation of water from the electrolyte. This results in a significantly shortened formation cycle and an electrolyte density within the range of 1.28 g / ml to 1.30 g / ml after formation. After formation, an appropriate amount of compounded electrolyte and a small amount of hexadecyl alcohol are added to the battery. The addition of propylene glycol to the compounded electrolyte improves the battery's low-temperature performance, and the final addition of a small amount of hexadecyl alcohol improves battery lifespan. Using this method, the battery formation cycle can be shortened by 35%-55%, and the deep cycle life of the formed battery is significantly improved.
[0027] This invention is mainly aimed at starting-type flooded lead-acid batteries, reducing the formation time of ordinary flooded batteries from about 10 hours to 4-5 hours, thereby greatly improving the production efficiency of flooded lead-acid batteries. Attached Figure Description
[0028] Figure 1 Examples C are Example 1, Example 2, Example 3, and Comparative Example C. 20 Capacity cycle curve. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] This invention relates to a method for forming a lead-acid battery, comprising the following steps:
[0031] ① Add acid to the lead-acid battery using a sulfuric acid solution with a density of 1.02 g / ml~1.06 g / ml and containing 0.5 wt%~1 wt% metal sulfate; ② Place the acid-added battery in a vacuum chamber, connect the charging circuit, and begin the formation process. The formation process includes two stages: a low-current charging stage to activate the electrodes, and a vacuum formation and rapid electrolyte evaporation stage. During the low-current charging stage to activate the electrodes, the absolute pressure inside the vacuum chamber is controlled at 40~60 kPa; during the vacuum formation and rapid electrolyte evaporation stage, the absolute pressure inside the vacuum chamber is controlled at 15~60 kPa; during the low-current charging stage to activate the electrodes, charge with a current of 0.02C20±0.5A for 0.2~0.3 h. Then, charge at a current of 0.15C20±3A for 0.2~0.5h, and control the electrolyte temperature at 45℃~60℃ during the formation process by setting the absolute pressure in the vacuum chamber. During the vacuum formation and rapid electrolyte evaporation stage, charge at a current of 0.45C20±5A for 2~2.5h, and then charge at a current of 0.35C20±5A for 2~2.5h, and control the electrolyte temperature at 50℃~65℃ during the formation process. By setting the charging current, charging time and absolute pressure in the vacuum chamber, the electrolyte density is made to reach 1.28g / ml~1.30g / ml, and the electrolyte level in the battery should not be lower than the upper edge of the plates at the end of the formation. ③ After formation, add a compound electrolyte to the battery; the weight of the compound electrolyte is 5wt%~10wt% of the weight of the acid added in step ①, the density of the compound electrolyte is 1.28g / ml~1.30g / ml, the compound electrolyte is prepared by adding propylene glycol to a 1.30g / ml sulfuric acid solution and stirring to mix well, the mass fraction of propylene glycol in the compound electrolyte is 2wt%~15wt% of the sulfuric acid solution, preferably 3wt%~8wt% of the mass fraction of propylene glycol in the compound electrolyte. ④ Add 1ml~5ml of hexadecyl alcohol heated to 60℃~70℃ to each cell of the battery.
[0032] Furthermore, during the vacuum formation and rapid electrolyte evaporation stages, the absolute pressure inside the vacuum chamber is controlled at 15~30 kPa. The metal sulfate is at least one of potassium sulfate and sodium sulfate, specifically potassium sulfate and sodium sulfate, with a mass ratio of sodium sulfate to potassium sulfate of 1:1~1:2. After adding the compound electrolyte in step ③, the electrolyte level inside the battery must submerge the battery's busbar and the butt-welded components connected to the busbar.
[0033] Example 1
[0034] A sulfuric acid solution with a density of 1.02 g / ml was used to add 0.5 wt% potassium sulfate and 0.5 wt% sodium sulfate. After mixing thoroughly, the solution was used to add acid to a 60 Ah starting type ordinary flooded lead-acid battery.
[0035] The acid-added batteries were placed in a vacuum chamber, and the charging circuit was connected to begin formation. First, during the electrode activation stage, the batteries were charged at 1.5A for 0.2 hours, followed by 12A for 0.2 hours, with the absolute pressure inside the vacuum chamber controlled at 60 kPa. Then, during the vacuum formation and rapid electrolyte evaporation stage, the absolute pressure inside the vacuum chamber was controlled at 30 kPa, and the batteries were charged at 27A for 2.5 hours, followed by 22A for 2 hours.
[0036] Add 3 wt% propylene glycol to a 1.30 g / ml sulfuric acid solution and stir rapidly to prepare a compound electrolyte. Add the compound electrolyte to the battery after formation is complete, ensuring the electrolyte level submerges the battery busbar and the butt-welded components connected to the busbar. Finally, add 1 ml of hexadecyl alcohol heated to 60°C to each cell of the battery.
[0037] Example 2
[0038] A sulfuric acid solution with a density of 1.05 g / ml was used to add 0.6 wt% potassium sulfate and 0.3 wt% sodium sulfate. After mixing thoroughly, the solution was used to add acid to a 60Ah starting type ordinary flooded lead-acid battery.
[0039] The acid-added batteries were placed in a vacuum chamber, and the charging circuit was connected to begin formation. First, a low-current charging stage was performed to activate the electrodes, charging at 0.7A for 0.3 hours, followed by charging at 9A for 0.5 hours, with the absolute pressure inside the vacuum chamber controlled at 40 kPa. Then, a vacuum formation and rapid electrolyte evaporation stage was performed, with the absolute pressure inside the vacuum chamber controlled at 15 kPa, charging at 32A for 2 hours, followed by charging at 26A for 2.2 hours.
[0040] Add 8 wt% propylene glycol to a 1.30 g / ml sulfuric acid solution and stir rapidly to prepare a compound electrolyte. Add the compound electrolyte to the battery after formation is complete, ensuring the electrolyte level submerges the battery busbar and the butt-welded components connected to the busbar. Finally, add 5 ml of hexadecyl alcohol heated to 70°C to each cell of the battery.
[0041] Example 3
[0042] A sulfuric acid solution with a density of 1.03 g / ml was used to add 0.3 wt% potassium sulfate and 0.2 wt% sodium sulfate. After mixing thoroughly, the solution was used to add acid to a 60 Ah starting type ordinary flooded lead-acid battery.
[0043] The acid-added batteries were placed in a vacuum chamber, and the charging circuit was connected to begin formation. First, a low-current charging stage was performed to activate the electrodes, charging at 1.1A for 0.25 hours, followed by charging at 10.5A for 0.35 hours, with the absolute pressure inside the vacuum chamber controlled at 50 kPa. Then, a vacuum formation and rapid electrolyte evaporation stage was performed, with the absolute pressure inside the vacuum chamber controlled at 60 kPa, charging at 30A for 2.2 hours, followed by charging at 24A for 2.5 hours.
[0044] Add 15wt% propylene glycol to a 1.30 g / ml sulfuric acid solution and stir rapidly to prepare a compound electrolyte. Add the compound electrolyte to the battery after formation is complete, ensuring the electrolyte level submerges the battery busbar and the butt-welded components connected to the busbar. Finally, add 3 ml of hexadecyl alcohol heated to 65°C to each cell of the battery.
[0045] Comparative Example
[0046] A sulfuric acid solution with a density of 1.19 g / ml was used to add 1.0 wt% sodium sulfate and mixed thoroughly before adding acid to a 60 Ah starting-type ordinary flooded lead-acid battery.
[0047] Connect the acid-added battery to the charging circuit to begin formation. First, charge at 6A for 0.5 hours, then charge at 19A for 6 hours, let stand for 0.5 hours, and then charge at 12.5A for 4 hours. After formation, pour out the acid from inside the battery, and then add a 1.33g / ml sulfuric acid solution to the battery. The electrolyte level should submerge the battery busbar and the butt welds connected to the busbar.
[0048] The following table shows a comparison of the formation time and formation charge of Examples 1, 2, and 3 with the existing formation process (comparative example). The formation time of this patented method is reduced by approximately 55% and the formation charge is reduced by approximately 30% compared with the existing process.
[0049]
[0050] The 60Ah starting-type ordinary flooded lead-acid batteries prepared in Examples 1, 2, and 3 were compared with the same type of battery prepared using the current formation process (comparative example) in a comparative test of their low-temperature starting capability at -18℃ and C. 20 Capacity cycle testing was conducted according to GB / T 5008.1-2023 "Starting Lead-acid Batteries - Part 1: Technical Conditions and Test Methods". Specific data are as follows, corresponding to C... 20 Capacity cycling curves are shown below. Figure 1 .
[0051]
[0052]
[0053] The low-temperature performance of the starting-type ordinary flooded lead-acid battery prepared using the method of this patent is basically the same as that of the battery using the current formation process, and it has better deep cycle life (although the initial capacity is slightly lower than that of the current process, it still meets the rated capacity requirements). It is of great significance in dealing with deep discharge of batteries caused by extreme working conditions.
[0054] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for forming a lead-acid battery, characterized in that: Includes the following steps: ① Add acid to a 60Ah starting-type flooded lead-acid battery using a sulfuric acid solution with a density of 1.02g / mL~1.06g / mL and containing 0.5wt%~1wt% metal sulfate; ② Place the acid-added battery in a vacuum chamber, connect the charging circuit and begin the formation process. The formation process consists of two stages: a small-current charging stage to activate the electrode, and a vacuum formation and rapid electrolyte evaporation stage. During the small-current charging stage to activate the electrode, the absolute pressure inside the vacuum chamber is controlled at 40~60 kPa. During the vacuum formation and rapid electrolyte evaporation stage, the absolute pressure inside the vacuum chamber is controlled at 15~60 kPa. ③ After the formation process is complete, add a compound electrolyte to the battery; ④ Add a small amount of hexadecyl alcohol to the battery; The small-current charging and electrode activation stage in step ② specifically involves: Charge at a current of 0.02C20±0.5A for 0.2~0.3h, then charge at a current of 0.15C20±3A for 0.2~0.5h. The electrolyte temperature during the formation process is controlled at 45℃~60℃ by setting the absolute pressure inside the vacuum chamber. The vacuum formation and rapid electrolyte evaporation stage in step ② specifically includes: Charge at a current of 0.45C20±5A for 2~2.5h, then charge at a current of 0.35C20±5A for 2~2.5h. During the formation process, the temperature of the electrolyte is controlled at 50℃~65℃. The electrolyte density after formation was in the range of 1.28 g / mL to 1.30 g / mL; Step ④ involves heating hexadecyl alcohol to 60°C~70°C and adding 1mL~5mL to each cell of the battery.
2. The lead-acid battery formation method as described in claim 1, characterized in that: During the vacuum formation and rapid evaporation of the electrolyte stage, the absolute pressure inside the vacuum chamber is controlled at 15~30 kPa.
3. The lead-acid battery formation method as described in claim 1, characterized in that: The metal sulfate in step ① is at least one of potassium sulfate and sodium sulfate.
4. The lead-acid battery formation method as described in claim 1, characterized in that: The metal sulfates in step ① are potassium sulfate and sodium sulfate, with the mass ratio of sodium sulfate to potassium sulfate being 1:1 to 1:
2.
5. The lead-acid battery formation method as described in claim 1, characterized in that: After adding the compound electrolyte in step ③, the electrolyte level inside the battery must submerge the battery busbar and the butt welds connected to the busbar.
6. The lead-acid battery formation method as described in claim 1, characterized in that: The weight of the compound electrolyte in step ③ is 5wt%~10wt% of the weight of the acid added in step ①; The density of the compound electrolyte is 1.28 g / mL to 1.30 g / mL; The compound electrolyte is prepared by adding propylene glycol to a 1.30 g / mL sulfuric acid solution and stirring to mix it. The mass fraction of propylene glycol in the compound electrolyte is 2 wt% to 15 wt% of the sulfuric acid solution.
7. The lead-acid battery formation method as described in claim 6, characterized in that: In the compound electrolyte, propylene glycol accounts for 3wt% to 8wt% of the sulfuric acid solution.
Citation Information
Patent Citations
Full negative pressure vacuum charging process and equipment for lead-acid batteries
CN115020837B
Manufacturing method of lead-acid storage battery
CN111628230A
Vacuum formation process and device for lead-acid storage battery
CN120149580A